2001
DOI: 10.1074/jbc.m103378200
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assembly and Recognition of Lys-63 Polyubiquitin Chains

Abstract: Polyubiquitin chains assembled through lysine 48 (Lys-48) of ubiquitin act as a signal for substrate proteolysis by 26 S proteasomes, whereas chains assembled through Lys-63 play a mechanistically undefined role in post-replicative DNA repair. We showed previously that the products of the UBC13 and MMS2 genes function in error-free post-replicative DNA repair in the yeast Saccharomyces cerevisiae and form a complex that assembles Lys-63-linked polyubiquitin chains in vitro. Here we confirm that the Mms2⅐Ubc13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
232
0
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(245 citation statements)
references
References 62 publications
7
232
0
5
Order By: Relevance
“…4g. In addition we observed a significant chemical shift perturbation in Phe 24 and weaker but noticeable shifts in peak positions for Gln 21 and Leu 18 , all located in helix 2, which is on the other side of the UBA molecule. These perturbations, also present in the monoUb-UBA complex (36), are probably caused by an indirect effect of the binding.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…4g. In addition we observed a significant chemical shift perturbation in Phe 24 and weaker but noticeable shifts in peak positions for Gln 21 and Leu 18 , all located in helix 2, which is on the other side of the UBA molecule. These perturbations, also present in the monoUb-UBA complex (36), are probably caused by an indirect effect of the binding.…”
Section: Resultsmentioning
confidence: 76%
“…E1 was from BostonBiochem Inc., and ethyleneimine was from Chemservice. Yeast Mms2 and Ubc13 were expressed and purified as in previous studies (21,22). Ub (K63C), Ub (K63R), and Ub (Asp 77 ) were expressed and purified as described in Haldeman et al (23).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we have not detected ISGylation of Gag or Tsg101, ISG15 was shown to conjugate to Ubc13 (7), Ub carrier protein E2. Ubc13 forms heterodimers with Mms2, and these catalyze assembly of K63-linked polyubiquitination (50). While this study was underway, it was shown that ISGylation of Ubc13 suppresses its ability to form thioester intermediates with Ub (51), which leads to inhibition of K63-linked ubiquitination.…”
Section: Discussionmentioning
confidence: 99%
“…Chains linked through Lys-48 are the principal signal for proteolysis by the proteasome (Hofmann and Pickart, 2001). In order to stabilize the ubiquitin-conjugated products, and ultimately to detect ubiquitin-conjugated LMP1, we generated an expression vector encoding ubiquitin mutated at lysine 48 (K48RUb).…”
mentioning
confidence: 99%